Analisis Penerimaan dan Penggunaan Teknologi Google Classroom Sebagai Media Pembelajaran Menggunakan Technology Acceptance Model (TAM) Dan Delone-McLean : Analisis Penerimaan dan Penggunaan Teknologi Google Classroom Sebagai Media Pembelajaran Menggunakan Technology Acceptance Model (TAM) Dan Delone-McLean - Heni Hermaliani, Eni; Nurhalimah (Jurnal Sistem Informasi Akuntansi (JASIKA), 2023)
Google Classroom is a free virtual classroom application that teachers and students can use to interact in carrying out the teaching and learning process online. SMP Negeri 1 Siabu has implemented google classroom as a learning medium. The problems that occur are obstacles when the online learning process takes place such as a lack of students' understanding of learning material, lost and slow internet signals, and limited internet quota. The purpose of this study was to analyze the acceptance and use of google classroom as a learning medium using the Technology Acceptance Model (TAM) and DeLone-McLean. The research was conducted using a quantitative approach, distributing online questionnaires to Siabu 1 Public Middle School students with 43 questions, and analyzing demographic data with Microsoft Excel 2016 while PLS-SEM analysis using SmartPLS 4. There were 10 variables used, and there were 13 variable relationship paths that were measured. The results of the 13 variable paths, 2 variable path relationships were declared insignificant and rejected in the acceptance and use of google classroom technology as a learning medium because the T-Statistics and P-Values (Perceived Usefulness -> User Satisfaction and System Quality -> Perceived Usefulness) were greater than 1.96 and less than 0.05, while 11 variable path relationships were declared significant and accepted in the acceptance and use of google classroom technology as learning media because the T-Statistics values were greater than 1.96 and P- Values less than 0.05. Thus the acceptance and use of Google Classroom technology as a learning medium can be accepted for the process of teaching and learning activities